'To shining clough': a trans-atlantic ecopoetic call and response. Issue 3 (3rd July 2019) - Street, Laura-Gray; Creamer, Anne-Marie
ABSTRACT: This article discusses how we, a US poet and a UK visual artist, opened an enmeshed space of creative practice in collaborating on a site-specific film, 'To Shining Clough'. The film's ground is literally the Peak District's Longdendale Valley, but it is also, by analogy, the shifting ground inherent in cross-disciplinary practice, particularly that predicated on ecology. As Tim Ingold argues, creative practice is synonymous with doing and making, with the thinking implicit in the doing. In doing together, even if asynchronously, we therefore thought together, even when transatlantically. Our collaboration involved dialogic improvisation and was informed by coincidence. It was also a form of correspondence, of co-responding to each other and to the texture and terrain of the Longdendale Valley. Taking as subject not just a location but the entangled fluxes present, 'To Shining Clough' embodies – as process and product – multiple ecopoetic contour lines.